(untitled) (Bangladesh Journal of Agricultural Research, 2011)
Twenty eight genotypes of potato representing different sources collected from TCRC, BARI, Gazipur were tested for genetic divergence utilizing multivariate analysis. The genotypes were grouped into five clusters. No relationship was found between genetic divergence and geographic distribution. Number of tubers per plant and yield contributed maximum, while average weight of a tuber and weight of tubers per plant contributed high towards total divergence which offered due attention to these characters while selecting for increased tuber yield. The inter-cluster distance (D2) was maximum (36.29) between III and IV. The highest and the lowest intracluster distances (D2) were 9.64 and 2.48 in cluster III and II, respectively. Keywords: Potato; selection; genetic divergence; cluster analysis; tuber yield. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9240 BJAR 2011; 36(1): 165-172